Protective Effect of Saikosaponin D against Streptozotocin-Induced Diabetic Nephropathy in Rats by Regulating the Oxidative Stress and Inflammatory Markers - Chen, Yan; Zhang, Guanglu; Liang, Rijing; Shen, Yao; Jiao, Xia (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Diabetic Nephropathy (DN) is a common problem in diabetes and is characterized by glomerular dysfunction, hyperfiltration, and ultimately kidney failure. Objectives The present study was intended to understand the salutary activities of Saikosaponin D in the Streptozotocin (STZ)-induced DN model. Materials and Methods 60 mg/kg of STZ was administered to the rats to initiate DN, and they were then treated with Saikosaponin D (10 and 20 mg/kg, respectively) for 10 weeks. Insulin and blood glucose levels were measured using kits. The levels of renal function markers creatinine, urinary protein, Blood Urea Nitrogen (BUN), inflammatory cytokines, Malondialdehyde (MDA), antioxidant enzyme Catalase (CAT), Superoxide Dismutase (SOD), and Glutathione Peroxidase (GPx) activities were analyzed by the corresponding assay kits. A histopathological analysis of kidney tissues was conducted on both control and treated rats. Results The Saikosaponin D treatment remarkably reduced blood glucose while boosting body weight and insulin in the DN rats. Creatinine, urinary protein, and BUN levels were considerably reduced by Saikosaponin D. It also diminished pro-inflammatory mediators and MDA levels while boosting antioxidant enzymes. The results of the histopathological analysis also revealed that Saikosaponin D considerably ameliorated STZ-induced histological damage in kidney tissues. Conclusion The current findings of this study demonstrate the therapeutic properties of Saikosaponin D in mitigating the development of DN in STZ-induced rats. Therefore, it was clear that Saikosaponin D could be a promising candidate to treat diabetic nephropathy.
Keywords: Diabetic nephropathy; Saikosaponin D; Oxidative stress; Creatinine; Insulin